2011
DOI: 10.1186/1756-3305-4-86
|View full text |Cite
|
Sign up to set email alerts
|

LeishVet guidelines for the practical management of canine leishmaniosis

Abstract: The LeishVet group has formed recommendations designed primarily to help the veterinary clinician in the management of canine leishmaniosis. The complexity of this zoonotic infection and the wide range of its clinical manifestations, from inapparent infection to severe disease, make the management of canine leishmaniosis challenging. The recommendations were constructed by combining a comprehensive review of evidence-based studies, extensive clinical experience and critical consensus opinion discussions. The g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
781
6
81

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 633 publications
(956 citation statements)
references
References 84 publications
30
781
6
81
Order By: Relevance
“…Em cada avaliação, os cães foram examinados individualmente e agrupados de acordo com o comprometimento clínico e com as anormalidades nos dados de patologia clínica, associados à LV, com base na categorização proposta pelo Leishvet group (Solano-Gallego et al 2011) adaptada para a realidade local (Quadro 1). Dessa forma, os cães foram classificados em três Estágios, em que o Estágio 1 foi composto por cães infectados e sem alterações clinicas e laboratoriais no momento do exame; o Estágio 2 correspondeu aos cães infectados e com alterações clínicas e laboratoriais brandas; o Estágio 3 incluiu cães infectados com alterações clínicas e laboratoriais severas.…”
Section: Methodsunclassified
See 1 more Smart Citation
“…Em cada avaliação, os cães foram examinados individualmente e agrupados de acordo com o comprometimento clínico e com as anormalidades nos dados de patologia clínica, associados à LV, com base na categorização proposta pelo Leishvet group (Solano-Gallego et al 2011) adaptada para a realidade local (Quadro 1). Dessa forma, os cães foram classificados em três Estágios, em que o Estágio 1 foi composto por cães infectados e sem alterações clinicas e laboratoriais no momento do exame; o Estágio 2 correspondeu aos cães infectados e com alterações clínicas e laboratoriais brandas; o Estágio 3 incluiu cães infectados com alterações clínicas e laboratoriais severas.…”
Section: Methodsunclassified
“…Diferentes estudos apontam medidas mais eficazes que a eutanásia para o controle e prevenção da LV, como o uso de coleiras impregnadas com inseticidas, vacinação e tratamento dos cães infectados (Reithinger et al 2004, Solano-Gallego et al 2009, Maroli et al 2010, Palatnik-de-Sousa 2012, Fernandes et al 2014. Na Europa, e em todos os países onde a LV é endêmica, a eutanásia de cães soropositivos não é utilizada como medida de controle da doença e os cães infectados são rotineiramente tratados (Gradoni et al 1987, Alvar et al 1994, Solano-Gallego et al 2009, Solano-Gallego et al 2011. No Brasil, apenas em 2016 foi autorizado a licença de uma droga para o tratamento da LVC, mas além desta ainda não estar sendo comercializada no país, o CFMV não reconhece esta autorização do MAPA/MS como válida, por não ter sido publicada no Diário Oficial, e continua declarando que, baseado na Portaria Interministerial 1426/2008, o tratamento da doença permanece proibido (CFMV 2016).…”
Section: Discussão E Conclusãounclassified
“…The most commonly observed are weight loss, lymphadenomegaly, splenomegaly, cutaneous and ocular lesions and impaired renal function (SOLANO-GALLEGO et al, 2011). Chronic kidney disease (CKD) is a severe result of disease progression and the main cause of death or an indication for euthanasia in infected dogs (PLANELLAS et al, 2009;SOLANO-GALLEGO et al, 2011;BANETH & SOLANO-GALLEGO, 2012;ROURA et al, 2013). While Cortadellas et al (2006) used the assessment of serum creatinine and UP/C and observed prevalence rates of CKD on the order of 49.5%, others based their assessments on postmortem histopathological studies and showed renal changes in nearly 100% of the dogs (NIETO et al, 1992;COSTA et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Infected dogs can be asymptomatic or present variable clinical signs. The most commonly observed are weight loss, lymphadenomegaly, splenomegaly, cutaneous and ocular lesions and impaired renal function (SOLANO-GALLEGO et al, 2011). Chronic kidney disease (CKD) is a severe result of disease progression and the main cause of death or an indication for euthanasia in infected dogs (PLANELLAS et al, 2009;SOLANO-GALLEGO et al, 2011;BANETH & SOLANO-GALLEGO, 2012;ROURA et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation